2010
DOI: 10.1038/nsmb.1833
|View full text |Cite
|
Sign up to set email alerts
|

DYRK1B-dependent autocrine-to-paracrine shift of Hedgehog signaling by mutant RAS

Abstract: Synergism between the RAS and Hedgehog (HH) pathways has been suggested for carcinogenesis in the pancreas, lung and colon. We investigated the molecular cross-talk between RAS and HH signaling and found that, although mutant RAS induces or enhances SHH expression and favors paracrine HH signaling, it antagonizes autocrine HH signal transduction. Activated RAS can be found in primary cilia, the central organelle of HH signal transduction, but functions in a cilium-independent manner and interferes with Gli2 fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
132
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 47 publications
8
132
0
Order By: Relevance
“…These pathways modulate GLI1 activity mainly via regulation of the expression of this transcription factor (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Here, we provide evidence of a novel regulatory mechanism involving the interaction of components of the TGF␤ pathway (SMAD proteins) modulating GLI1 activity in cancer cells.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These pathways modulate GLI1 activity mainly via regulation of the expression of this transcription factor (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Here, we provide evidence of a novel regulatory mechanism involving the interaction of components of the TGF␤ pathway (SMAD proteins) modulating GLI1 activity in cancer cells.…”
Section: Discussionmentioning
confidence: 76%
“…These findings support the notion that increased expression of GLI1 is sufficient for the development of a subset of tumors. GLI1 activity is regulated by different oncogenic cascades, including the HEDGEHOG, EGFR, RAS, and TGF␤ pathways (1,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It has been demonstrated that malignant transformation induced by some of these cascades requires an intact GLI1 transcriptional activity (17,20,21).…”
mentioning
confidence: 99%
“…In addition, results from studies using high doses of cyclopamine may be confounded by the off-target effects of cyclopamine at concentrations in the micromolar range. In some tumors where paracrine and autocrine Hh signaling coexists, the balance between the two may regulate cancer progression (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, enforced expression of an active GLI factor in pancreatic epithelial cells promotes tumorigenesis in mice (Pasca di Magliano et al, 2006). In the canonical Hedgehog-GLI pathway, GLI activity is dependent upon signaling by Hedgehog through PTCH1 and SMO, whereas in PDA cells GLI1 is instead maintained by activated KRAS (Hingorani et al, 2005;Pasca di Magliano et al, 2006;Ji et al, 2007;Nolan-Stevaux et al, 2009;Tian et al, 2009;Lauth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although GLI1 is expressed in both epithelial PDA cells and stromal cells, a cell autonomous role within carcinoma cells appears central to the pathogenesis of this disease (Feldmann et al, 2007;NolanStevaux et al, 2009;Tian et al, 2009;Lauth et al, 2010). Indeed, suppression of GLI1 in human PDA cells leads to loss of malignant properties Feldmann et al, 2007;Nolan-Stevaux et al, 2009).…”
Section: Introductionmentioning
confidence: 99%